Permafrost Microbial Community Structure Changes Across the Pleistocene-Holocene Boundary - Saidi-Mehrabad, Alireza; Neuberger, Patrick; Hajihosseini, Morteza; Froese, Duane; Lanoil, Brian D. (Frontiers in Environmental Science, 2020)
Despite the presence of well-documented changes in vegetation and faunal communities at the Pleistocene-Holocene transition, it is unclear whether similar shifts occurred in soil microbes. Recent studies do not show a clear connection between soil parameters and community structure, suggesting permafrost microbiome-climate studies may be unreliable. However, the majority of the permafrost microbial ecological studies have been performed only in either Holocene- or Pleistocene-aged sediments and not on permafrost that formed across the dramatic ecosystem reorganization at the Pleistocene-Holocene transition. In our study, we used permafrost recovered in proximity to the Pleistocene-Holocene transition subsampled under strict sterile conditions developed for ancient DNA studies. Our ordination analyses of microbial community composition based on 16S RNA genes and chemical composition of the soil samples resulted into two distinct clusters based on whether they were of late Pleistocene or Holocene age, while samples within an epoch were more similar than those across the boundary and did not result in age based separation. Between epochs, there was a statistically significant correlation between changes in OTU composition and soil chemical properties, but only Ca and Mn were correlated to OTU composition within Holocene aged samples; furthermore, no chemical parameters were correlated to OTU composition within Pleistocene aged samples. Thus, the results indicate that both soil chemical and microbial parameters are fairly stable until a threshold, driven by climate change in our study, is crossed, after which there is a shift to a new steady state. Modern anthropogenic climate change may lead to similar transitions in state for soil biogeochemical systems and microbial communities in Arctic regions.